PENGARUH KEPEMIMPINAN SITUASIONAL TERHADAP SEMANGAT KERJA PERAWAT RUMAH SAKIT SANTA MARIA PEKANBARU - Anggrenni, Dian Prapty; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to find the implications of leadership on keep spirit of nurses in Santa Maria Hospital Pekanbaru. Leadership as an independent variable (X) consist of leadership telling, selling, participating, and delegating. And keep spirit as the dependent variable (Y) cosist pf salary, incentive and allowance and improvement of welfare.The research used sample of the nurses in Santa Maria Pekanbaru. The number of this sample is 67 persons with slovin. This research is also used Stratified proportional random sampling. Data of this research is primary data, with spread questions to the nurses. The data analysis of this research is statistical analysis with SPSS program.This research shows that leadership as independent variable is positive implications for the nurses who worked at Santa Maria Hospital Pekanbaru as coefficeents determination value (R2) is 0,40, it mens that 40% and 60% is not served in this researvh.Keyword : Leadership Situational, Keep sprit, nurses